Spatial Vision in Bombus terrestris - Chakravarthi, Aravin; Baird, Emily; Dacke, Marie; Kelber, Almut (Frontiers in Behavioral Neuroscience, 2016)
Bombus terrestris is one of the most commonly used insect models to investigate visually guided behavior and spatial vision in particular. Two fundamental measures of spatial vision are spatial resolution and contrast sensitivity. In this study, we report the threshold of spatial resolution in B. terrestris and characterize the contrast sensitivity function of the bumblebee visual system for a dual choice discrimination task. We trained bumblebees in a Y-maze experimental set-up to associate a vertical sinusoidal grating with a sucrose reward, and a horizontal grating with absence of a reward. Using a logistic psychometric function, we estimated a resolution threshold of 0.21 cycles deg-1 of visual angle. This resolution is in the same range but slightly lower than that found in honeybees (Apis mellifera and A. cerana) and another bumblebee species (B. impatiens). We also found that the contrast sensitivity of B. terrestris was 1.57 for the spatial frequency 0.09 cycles deg-1 and 1.26. for 0.18 cycles deg-1.